Bipolar Latissimus Dorsi Transfer through a Single Incision: First Key–Step in Poland Syndrome Chest Deformity. Issue 8 (August 2016) - Watfa, William; di Summa, Pietro G.; Raffoul, Wassim
Abstract : Summary: Poland syndrome is a rare congenital anomaly characterized by a unilateral congenital absence of the sternocostal head of the pectoralis major muscle. The absence of the pectoralis major does not only result in chest asymmetry but also in a missing anterior axillary fold, which is essential for natural anatomical appearance in both male and female patients. In Poland syndrome patients, we perform bipolar latissimus dorsi flap transfer, which can be associated with a sublatissimus implant in women. All procedures are performed through a single short midaxillary incision, and tendon translocation in this technique allows the creation of the anterior axillary fold and thus a natural chest appearance. Moreover, this technique can be performed by any plastic surgeon operating under a basic operating room setting. Abstract : Supplemental Digital Content is available in the text.